(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The advanced wireless communication system uses the new technology, preparing the limited radio spectrum and its low expensive resource. The Scenario of Wireless communication is needed for the flexible mechanism with available time and frequency resources. The OFDM system, which is a multicarrier process with a remote framework in Long Term Evolution (LTE), 4G, and 5G. Using of UFMC(Universal_Filtered_Multicarrier)system with OFDM system symmetrical recurrence division multiply with modulation system and the correlation between them. Using of UFMC system with QAM into the MIMO system the result of subchannel, the model channel correlation recreated in “ A Simulational Performance of 5G MIMO Systems applying UFMC (Universal_Filtered_Multicarrier ) Study” result shown in MATLAB.